Problematika Penerapan Hukum Perkawinan Islam di Era Digital: Studi Kasus Pernikahan Online di Indonesia - Ahmad Alimuddin (Al Fuadiy Jurnal Hukum Keluarga Islam, 2024)
The advancement of technology in the digital era has brought significant changes to various aspects of life, including the practice of Islamic marriage law in Indonesia. One emerging phenomenon is online marriage, which has been increasingly conducted, particularly during the COVID-19 pandemic. This study aims to analyze the legal issues surrounding the practice of online marriage, evaluate its validity according to Islamic law, and examine the need for regulation within the framework of positive law. The research method employed is a policy analysis approach, with data collected through literature studies and interviews with relevant stakeholders. The findings reveal that the practice of online marriage faces several challenges, such as legal uncertainty due to the absence of clear regulations in the Marriage Law and the Compilation of Islamic Law (KHI). Additionally, the validity of virtual marriage contracts remains a subject of debate, as they do not always fulfill the essential conditions of marriage, such as ittihadul majlis (unified session) and the physical presence of witnesses. From a social perspective, this practice also encounters resistance, as it is perceived to contradict the traditional values of Indonesian society. This study recommends the necessity of comprehensive regulations and collaboration between the government, religious scholars, and technology experts to integrate Islamic principles with technological advancements. Through a holistic approach, online marriage can be legally recognized and socially accepted, providing legal certainty and protecting the rights of individuals in the digital era.